Exploration of ethnomathematics research in Indonesia 2010-2023 - Anggun Badu Kusuma; Farida Hanum; Agus Maman Abadi; Ahmad Ahmad (Jurnal Infinity, 2024)
Ethnomathematics is the finding of mathematics in the cultural values of a place. Indonesia has many kinds of cultures, and ethnomathematics research has been done in some areas of Indonesia. This study aims to identify the cultural forms and mathematical materials found in ethnomathematical research in Indonesia. The research method used is a literature review. The stages of the research method included selecting a topic, developing tools of argumentation, searching the literature, surveying the literature, critiquing the literature, and writing the thesis. The instruments used were Google Scholar, the search engine, and the NVivo application. The number of articles analyzed was 88 articles. These articles represent the culture spread across 34 provinces of Indonesia. The research results obtained are cultural forms containing mathematical material, including ideas, activities, and artifacts. Mathematical materials explored in these cultures include statistics, trigonometry, vector, algebra, arithmetic, one-dimensional geometry, two-dimensional geometry, three-dimensional geometry, coordinate geometry, transformation geometry, calculus, logic, and opportunity. The complexity of the culture and material found in mathematics shows that ethnomathematical research can be developed in all forms of culture and applied in various mathematics learning materials.